2020
DOI: 10.1111/jdv.16236
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse drug reaction after continuous subcutaneous apomorphine infusion

Abstract: breastfeeding period was uncomplicated during the next 4 months of observational period. The European Medicines Agency (EMA) reported 2017 data from one phase-2b and three phase-3 studies including 2500 AE patients, whereby 23 pregnancies of female patients treated with dupilumab resulted in deliveries of eight healthy babies (1 twin birth), two induced abortions and six spontaneous abortions. In two of these six cases, patients had at least one risk factor for abortion (i.e. elevated parathyroid hormone, clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Common published adverse events of CSAI in major case series and case reports are listed in Table 4 and Table S1 18,22,24–26,29,52–71 . In an audit on reasons for discontinuing therapy of 107 patients over 10 years, Tyne et al 18 reported that therapy was discontinued in 16% of patients (with some opting for intermittent injections, and 10 going on to DBS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common published adverse events of CSAI in major case series and case reports are listed in Table 4 and Table S1 18,22,24–26,29,52–71 . In an audit on reasons for discontinuing therapy of 107 patients over 10 years, Tyne et al 18 reported that therapy was discontinued in 16% of patients (with some opting for intermittent injections, and 10 going on to DBS).…”
Section: Resultsmentioning
confidence: 99%
“…Common published adverse events of CSAI in major case series and case reports are listed in Table 4 and Table S1. 18,22,[24][25][26]29,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] In an audit on reasons for discontinuing therapy of 107 patients over 10 years, Tyne et al 18 reported that therapy was discontinued in 16% of patients (with some opting for intermittent injections, and 10 going on to DBS). Although nine patients died during the audit periods, none of the deaths were attributed to CSAI.…”
Section: Causes For Discontinuation and Adverse Events Of Csaimentioning
confidence: 99%